2016
DOI: 10.1039/c5nj02349a
|View full text |Cite
|
Sign up to set email alerts
|

Convenient preparation of Pd/RGO catalyst for the efficient hydrodechlorination of various chlorophenols

Abstract: Highly active Pd/RGO (RGO, reduced graphene oxide) was easily prepared by a one pot co-reduction of Pd ions and GO using NaBH4. The as-prepared catalyst exhibited excellent reactivity towards the degradation of chlorophenols under mild conditions without additives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The lower intensity of the peaks associated with the oxygen-containing groups (e.g., the O-H stretching vibration at 3426 cm −1 , C=O stretching and C-O stretching bands at 1706 cm −1 and 1069 cm −1 , respectively, and the C=O vibrations and C-O group at the edges of GO at 1287 and 1040 cm −1 , respectively) were observed for rGO. Low peak intensities of the oxygen-containing groups on the rGO surface are indicative of the successful reduction of GO [63]. Accordingly, based on this characterization, it was concluded that the desired Pd/Al and Pd/rGO catalysts were successfully obtained.…”
Section: Resultsmentioning
confidence: 72%
“…The lower intensity of the peaks associated with the oxygen-containing groups (e.g., the O-H stretching vibration at 3426 cm −1 , C=O stretching and C-O stretching bands at 1706 cm −1 and 1069 cm −1 , respectively, and the C=O vibrations and C-O group at the edges of GO at 1287 and 1040 cm −1 , respectively) were observed for rGO. Low peak intensities of the oxygen-containing groups on the rGO surface are indicative of the successful reduction of GO [63]. Accordingly, based on this characterization, it was concluded that the desired Pd/Al and Pd/rGO catalysts were successfully obtained.…”
Section: Resultsmentioning
confidence: 72%
“…Next, the catalytic properties of the Pd‐RGO synthesized in the manner shown in Figure were tested through the Suzuki–Miyaura reaction. In previous studies, large amounts of reducing agents were used in the preparation of Pd‐RGO, which required a purification process before being used as a catalyst . However, we expected that the Pd‐RGO could be used immediately without any purification, if the reduction was conducted with a minimum amount of reducing agent and at a high temperature.…”
Section: Catalytic Activity Of Pd‐rgos Depending On the Reduction Temmentioning
confidence: 99%
“…Moreover, the resulting products including phenol and 4-aminophenol (4-AP) are useful chemicals that can be applied in various applications [ 15 ]. Considerable research efforts have been devoted to developing supported catalysts with Pd nanoparticles as the active sites for HDC and hydrogenation reactions [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. However, one limitation of the HDC of 4-CP reaction is that the catalysts suffer from serious deactivation by HCl, which is generated as a byproduct during the HDC process through the scission of C–Cl bonds in 4-CP.…”
Section: Introductionmentioning
confidence: 99%